Education For Healthy Latrine In Kampala Hamlets, Limapoccoe Village, Maros Regency - Wijaya, Dian Rezki (Tadulako University, 2023)
Permanent healthy latrines are latrines that already use a goose-neck construction and are located inside the house. In 2020, 72.3% of Indonesian families have used permanent healthy latrines. The remaining 18.5% use semi-permanent healthy latrines and 9.2% use sharing/communal latrines. This research uses quantitative research with purposive sampling technique. This study uses quasi-experimental designs with a one-group pretest-posttest. The research population is the population living in Kampala Hamlets, Limapoccoe Village. Respondents in this study amounted to 30 respondents. The variables seen in this study are Knowledge and Attitudes Regarding the Healthy Latrine. This research was conducted in December 2021. Data processing was carried out in a descriptive analytic manner with the Wilcoxon test. The results of the research conducted on the level of community knowledge in the Kampala hamlet regarding healthy latrine there was a significant difference (p value 0.00) in the knowledge, attitudes and actions of the community before and after the counseling was carried out. It is necessary to have an integrated counseling program carried out by the puskesmas, posyandu cadres, and Kampala village government so that there is an increase in knowledge, attitudes and actions of healthy latrine.